Bichromophoric Sensors for Ratiometric Measurements of Molecular Microenvironments through the Interplay of Charge Transfer and Energy Transfer Channels. Issue 12 (29th October 2018) - Arroyo‐Pieck, Andres; Araiza‐Olivera, Daniela; Peon, Jorge
Abstract: A new molecular architecture was designed to amplify the sensitivity of bichromophoric probes, in which two sequential kinetic competitions of photophysical channels were used to define the emission yield of the lower energy chromophore. Additionally, the emission from both chromophores can be used for ratiometric measurements, which are concentration independent. Two sensors were synthesized to demonstrate the concept, coupling a boron‐dipyrromethene (BODIPY) dye and a cyanine dye. Both the energy transfer from the BODIPY to the cyanine and the cyanine radiative channel compete with a charge transfer state formation, giving the cyanine emission intensity a twofold dependence on polarity. This was confirmed with steady state and time‐resolved spectroscopies. Also, the large spectral gap between the two emissions (approx. 280 nm) makes the ratiometric measurements crosstalk‐free. The use of the sensors in live cells was demonstrated through the staining and imaging of SK‐LU‐1 lung cells under normal and apoptotic conditions. Abstract : Two channels : A new molecular architecture enhances the sensitivity of bichromophoric fluorescent probes to changes in their environment. This comes from the tandem kinetic competition between the formation of charge transfer states and the energy transfer between the chromophores and the fluorescence emission of the molecule.